IMPLEMENTATION OF THE PROJECT TO STRENGTHEN THE PROFILE TF PANCASILA STUDENTS IN DRIVING SCHOOLS IN SAMARINDA CITY - Khusnul Khotimah; Aisyah Trees Sandy; Bella Dinda Septania; Agustang Agustang; Muhammad Hari Akbar; Muhammad Ali Akbar (JURNAL NALAR PENDIDIKAN, 2024)
The Project to Strengthen the Profile of Pancasila Students (P5) is an effort to translate the goals of national education into six dimensions, namely: 1) faith, devotion to God Almighty, and noble character, 2) independence, 3) cooperation, 4) global diversity, 5) critical thinking, and 6) creativity. This research aims to determine the implementation of P5 in Sekolah Penggerak Samarinda. Qualitative methods were used by conducting interviews with principals, teachers, and P5 project leaders in 5 Sekolah Penggerak. The research findings show that P5 has been implemented in Sekolah Penggerak with different themes and patterns. Common themes include local wisdom, entrepreneurship, and sustainable lifestyles. The implementation of P5 still does not follow the implementation stages according to the P5 guidelines and is implemented with different patterns integrated with and outside of learning. Evaluating continues to focus on assessing the final product rather than the working process.